Siberian heat extremes caused by Eurasian atmospheric teleconnections and amplified by local land surface conditions - Choi, Nakbin; Lee, Myong-In; Tak, Sunlae; Cha, Dong-Hyun; Watanabe, Masahiro (Environmental Research Letters, 2025)
Abstract This study aims to examine the mechanisms that drive extreme heat events in Siberia during boreal spring. The results from this study suggest that the upper-level atmospheric waves across Eurasia induced by the warm sea surface temperature (SST) in the eastern North Atlantic and large snow melting in southern Siberia are responsible for a large temperature increase in Siberia. These suggested mechanisms are examined by both observed data analysis and ideal numerical model simulations, which reasonably explain the record-breaking extreme heat events in 1997 and 2020. Future climate change scenarios simulated by a global climate model with large ensembles project a much larger increase in surface air temperature in Siberia compared to the surrounding area. Under future climate conditions, with significantly warmer SSTs in the eastern Atlantic and increased snowmelt in southern Siberia, the risk of extreme heat events in Siberia is expected to rise considerably. This is due to the enhanced large-scale atmospheric teleconnections and intensified local atmosphere-land feedback that will result from these changes.